If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -1(-86) = 52 Multiply -1 * -86 2p + 86 = 52 Reorder the terms: 86 + 2p = 52 Solving 86 + 2p = 52 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-86' to each side of the equation. 86 + -86 + 2p = 52 + -86 Combine like terms: 86 + -86 = 0 0 + 2p = 52 + -86 2p = 52 + -86 Combine like terms: 52 + -86 = -34 2p = -34 Divide each side by '2'. p = -17 Simplifying p = -17
| 3600=200x-x^2 | | -4l+(-25)=55 | | 3x-13y=2forwhy | | 4(x-2)+2x=3(x-1)-11 | | -3e-72=-18 | | -214+-8(2x-3)=-334 | | 3v-36=-42 | | 10x+5=12y+5 | | 15y+20= | | 4r+(-12)=48 | | 15y/4=90 | | 2x-6+4x+28=6x+22 | | 3(x+1)x+4(x+3)=22 | | 4(2x-y)=2y+5 | | 147.1875=3r(3.14r^2) | | 0.4(x+25)-3=0.2(7x+10) | | 13x-4x=-63 | | 3y+4z=9fory | | 8x=6y+5 | | 22-6y+y^2-14=0 | | 83=15+2(x) | | -8a=-8b | | (3)(2x-4)+2(2x-4)-x=-17 | | 12=15*Z-1/5 | | x+(-40)=y | | X^2+4x-62.5=0 | | 15=5+9(3) | | b+-4=-4 | | -5x=-5y | | g/3-0.9=-.4 | | 85=17p | | 7x^4z^3/28y^3 |